Mathematical models for the extraction of volatile oils and active principles from medicinal and aromatic plants. A review - Tăbărașu, Ana-Maria; Anghelache, Dragoș- Nicolae; Găgeanu, Iuliana; Biriș, Sorin-Ștefan; Constantin, Ana-Maria; Marin, Florin; Hâncu, Iulian (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Active principles cand be extracted from medicinal and aromatic plants using different methods depending on the type and condition of the plant, the active compounds to be obtained, the nature of the solvent used in the whole process (water, alcohol). State-of-the-art methods for the separation and quantification of bioactive compounds from plant materials have led to rapid and efficient development in the pharmaceutical, food and agricultural sectors. Compared to the extraction techniques in the past, it is noticed that the ones currently used are techniques with considerable selectivity and as a result, by using non-toxic solvents, they have the characteristics of ecological techniques. Recent research studies describe mathematical models that have recorded the highest extraction rate and capacity of essential oils and volatile compounds from medicinal and aromatic plants. This paper presents a review of different types of mathematical models used for the purpose of obtaining active compounds from plants in the largest possible quantity.